Studies on the Hypercoagulable State - Kropatkin, M. L; Izak, G (Thrombosis and Haemostasis, 1968)
The intravenous injection of fibrinogen was associated with a prolonged hyperfibrinogenemia in the rabbit, out of proportion to the amount of fibrinogen administered. Factors V, II, VII and X activities were found to be elevated in the plasma simultaneously.A similar pattern of changes was observed in the rabbit after the recovery period from thrombin-induced defibrination.Based on the observations reported here, it was suggested that some fibrinogen or fibrin break-down products deliver the stimulatory message to the liver for increased fibrinogen production.The possible relationship between these observations and hypercoagulable state has been discussed.